Sleepiness: What it is, what causes it, and how measure it - Rosales Mayor, Edmundo (2010)
Somnolence, defined as a tendency to fall asleep, may be the main symptom in many different conditions. Sleep deprivation is the most common cause for somnolence. Measuring or assessing somnolence may be complicated, because of its operational definitions. Most commonly used instruments include self-administered questionnaires measuring subjective somnolence. Excessive somnolence has an impact on mental and physical health of affected persons, so it is important that healthcare professionals should always be able to properly assess this condition, and to determine its cause. If cases are troublesome or complicated, then the patient may be sent to a specialist in sleep medicine.